Surface protection against corrosion of Ni turbine blades by electrophoretic deposition of MnO2, TiO2 and TiO2–C nanocoating. Issue 52 (24th November 2022) - Yousif, Qahtan. A.; Majeed, Mohammad N.; Bedair, Mahmoud A.
Abstract : MnO2, TiO2 and TiO2 –C nanomaterials have been coated on the nickel alloy, which is the composition of turbine blades, by the electrophoretic deposition technique for protection against the corrosion process. Abstract : The turbine blades of turbochargers are corroded after being cleaned with water in the presence of gasses produced during the combustion of heavy fuel. For that, manganese oxide (MnO2 ), titanium dioxide (TiO2 ), and titanium oxide–graphene (TiO2 –C) nanomaterials have been coated on the nickel alloy, which is the composition of turbine blades, by the electrophoretic deposition technique for protection against the corrosion process. The anticorrosion performance of nanomaterial coatings has been investigated using electrochemical methods such as open circuit potential, potentiodynamic, electrochemical impedance, and linear polarization resistance in a 1 M H2 SO4 solution saturated with carbon dioxide. The corrosion rate of nanomaterial-coated Ni-alloy was lower than bare alloy, and potential corrosion increased from −0.486 V for uncoated Ni-alloy to −0.252 V versus saturated calomel electrode for nanomaterial coated Ni-alloy electrodes. Electrochemical measurements show that TiO2 coated Ni-alloy corrosion has good protective qualities, with an efficiency of 99.91% at 0.146 mA cm 2 current density in sulfuric acid media. The findings of this study clearly show that TiO2 has a high potential to prevent nickel alloy turbine blades from corrosion in acidic media. Furthermore, the surface morphologies have revealed that TiO2 and MnO2 coatings might successfully block an acid assault due to the high adhesion of the protective layer on the nickel alloy surface. The use of X-ray diffraction (XRD) enhanced the various measures used to determine and study the composition of the alloy surface's protective coating.